Cancer in the first 18 months of life - Andrea Urtasun Erburu; Maria José Herrero Cervera; Adela Cañete Nieto (Anales de Pediatría (English Edition), 2020)
Introduction: Oncological-haematological disease continues to be the first cause of non-traumatic mortality in childhood, as well as a significant cause of morbidity. The patient less than 18-months-old has special clinical, diagnostic, and therapeutic features that all paediatricians are interested in determining, with the aim of achieving greater survival and a lower morbidity throughout the lives of their patients. Material and methods: A retrospective, descriptive study was carried out using the clinical, diagnostic, and therapeutic variables in patients less than 18-months-old diagnosed with an oncological-haematological that received chemotherapy in a Paediatric Oncology Unit between January 2007 and August 2019. Results: A total of 72 patients were diagnosed with 76 cancers that required chemotherapy. The most common cancer was leukaemia (21 patients), followed by neuroblastoma (15 patients), and tumours of the central nervous system (12 patients). The presentation of “life-threatening symptoms” was seen in 20.8% of cases, particularly in tumours of neural origin (13/15). Although 18% of patients showed no symptoms on diagnosis, just over half (51%) of the diagnoses took place in the “advanced stages”. Particularly in the case of solid tumours in which 23.6% were diagnosed with metastases. A significant percentage of genetic alterations implicated in the aetiopathogenesis of the different cancers were found. Conclusions: Cancer in the first stages of life is a diagnostic and therapeutic challenge due to its phenotypical diversity, its genetic load, and its therapeutic difficulties. Knowledge of its particular features is essential for its early and effective approach. Resumen: Introducción: La enfermedad oncohematológica continúa siendo la primera causa de mortalidad no traumática en la infancia y una importante causa de morbilidad. El paciente menor de 18 meses presenta particularidades clínicas, diagnósticas y terapéuticas que es interesante conocer por todo pediatra, con el fin de lograr una mayor supervivencia y una menor comorbilidad a lo largo de su vida. Material y métodos: Estudio descriptivo retrospectivo de variables clínicas, diagnósticas y terapéuticas en pacientes menores de 18 meses diagnosticados de enfermedad oncohematológica que reciben quimioterapia en una Unidad de Oncología Pediátrica entre enero 2007 y agosto 2019. Resultados: 72 pacientes fueron diagnosticados de 76 neoplasias que precisaron quimioterapia. La neoplasia de mayor incidencia fue la leucemia (21 pacientes), seguida del neuroblastoma (15 pacientes) y los tumores sistema nervioso central (12 pacientes). La presentación con “síntomas amenazantes para la vida” tuvo lugar en el 20,8% de los afectados, especialmente en tumores de estirpe neural (13/15). 18% de pacientes no presentaron síntomas al debut. El 51% de los diagnósticos totales tuvieron lugar en “estadios avanzados”. Concretamente en el caso de los tumores sólidos, el 23,6% de los debuts presentaron metástasis. Se aislaron importantes porcentajes de alteraciones genéticas implicadas en la etiopatogenia de las diferentes neoplasias. Conclusiones: El cáncer en la primera etapa de la vida supone un reto diagnóstico y terapéutico por su diversidad fenotípica, su carga genética y sus dificultades terapéuticas. El conocimiento de sus particularidades es fundamental para un abordaje precoz y eficaz.